A proposed lectin‐mediated mechanism to explain the in Vivo antihyperglycemic activity of γ‐conglutin from Lupinus albus seeds. Issue 11 (18th September 2021) - Grácio, Madalena; Rocha, João; Pinto, Rui; Boavida Ferreira, Ricardo; Solas, João; Eduardo‐Figueira, Maria; Sepodes, Bruno; Ribeiro, Ana Cristina
Abstract: Experiments conducted in vitro and in vivo, as well as clinical trials for hypoglycemic therapeutics, support the hypoglycemic properties of the lectin γ‐conglutin, a Lupinus seed storage protein, by a mechanism not yet been clarified. Structural studies established that binding of γ‐conglutin, in native and denatured form, to insulin occurs by a strong binding that resists rupture when 0.4 M NaCl and 0.4 M galactose are present, suggesting that strong electrostatic interactions are involved. Studies on binding of γ‐conglutin in native and denatured form to HepG2 membrane glycosylated receptors were conducted, which reveal that only the native form of γ‐conglutin with lectin activity is capable of binding to these receptors. Glycosylated insulin receptors were detected on purified HepG2 cell membranes and characterized by 1D and 2D analyses. Preclinical assays with male mice (CD‐1) indicated that native and denatured γ‐conglutins display antihyperglycemic effect, decreasing glucose in blood comparable after 120 min to that exhibited by the animal group treated with metformin, used to treat T2D and used as a positive control. Measurement of organ injury/functional biomarkers (hepatic, pancreatic, renal, and lipid profile) was comparable to that of metformin treatment or even better in terms of safety endpoints (pancreatic and hepatic biomarkers). Abstract : A lectin mechanism to understanding the antihyperglycemic activity of gamma conglutin. The involved molecules in hypoglycemic activity are majority glycoproteins, excepted insulin.